Specification for unplasticized PVC underground drain pipe and fittings (BSI, 1973)
Unplasticized polyvinyl chloride, Polyvinyl chloride, Polymers, Plastics, Drainpipes, Pipes, Pipe fittings, Drainage, Underground, Colour, Diameter, Thickness, Length, Dimensions, Sampling methods, Marking, Tensile strength, Elongation at fracture, Testing conditions, Design, Acid-resistance tests, Alkali-resistance tests, Test specimens, Thermal testing, Test equipment, Impact testing, Hydraulic tests, Pressure testing, Crushing tests, Mechanical testing, Deflection tests, Thermal-cycling tests, Stress relieving